"Exploring the Influence of Employee Demographics on Engagement and Organizational Culture: A Gender Perspective" - Dr. Navleen Kaur; Ravneet Kaur (Educational Administration: Theory and Practice, 2024)
HR practitioners and business leaders are focused on establishing positive workplace atmospheres using cultural practices. Turner, J. W., & Jones, S. A. (2012). This article aims to further such efforts in our understanding of how Gender, as a demographic attribute, impacts perceptions, behavior, and habits of employees within an organization, such as in engagement levels and organizational culture and its perception. Additionally, other studies include the impact of Gender on an employee's perception of the organization. Positive change in organizational culture is enhanced by changing gender balance, therefore fostering development. Burke, R. J. (2014). By looking at the quantitative data collected from employees of various industries, such biases in the workplace can be avoided. Employees, gender-related ones, in particular, were able to restrict their engagement with other colleagues during and even after policies were created regarding workplace participation and inclusivity. Berghe, L. V. (2012). Cross-examination of decision-making involvement, work satisfaction, and inclusiveness led to a better understanding of employee engagement through Gender and other influences. The research primarily takes into consideration one demographic characteristic – Gender, focusing subsequently on its role in team collaboration, leadership type, and workplace in general.